2017
DOI: 10.1371/journal.pone.0177343
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ANP32B exerts anti-apoptotic effects in hepatocellular carcinoma

Abstract: The acidic (leucine-rich) nuclear phosphoprotein 32 family member B (ANP32B), a highly conserved member of the acidic nuclear phosphoprotein 32 (ANP32) family, is critical for the development of normal tissue. However, its role in the development of hepatocellular carcinoma (HCC) is controversial. In this study, we elucidated the role of ANP32B in HCC cell lines and tissues. ANP32B expression in HCC cell lines was modulated using siRNA and ANP32B expression plasmids and lentiviruses. The levels of apoptosis-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…For example, the transcription factor Krüppel‐like factor 5 can recruit ANP32B to the promoter region of the platelet‐derived growth factor subunit A gene to suppress its expression by incorporating histones and inhibiting its acetylation . On the other hand, it has also been suggested that ANP32B may exert an antiapoptotic function due to the observed correlation between its downregulation in hepatocellular carcinoma cells and the progression of the disease, characterized by the enhanced phosphorylation/activation of Bcl‐2‐associated death promoter and the upregulation of Bax . In a similar fashion to SET/TAF‐Iβ and NRP1, C c may be regulating ANP32B function within the nucleus.…”
Section: Nuclear Localization Is What Matters: Converting CC From a Kmentioning
confidence: 99%
“…For example, the transcription factor Krüppel‐like factor 5 can recruit ANP32B to the promoter region of the platelet‐derived growth factor subunit A gene to suppress its expression by incorporating histones and inhibiting its acetylation . On the other hand, it has also been suggested that ANP32B may exert an antiapoptotic function due to the observed correlation between its downregulation in hepatocellular carcinoma cells and the progression of the disease, characterized by the enhanced phosphorylation/activation of Bcl‐2‐associated death promoter and the upregulation of Bax . In a similar fashion to SET/TAF‐Iβ and NRP1, C c may be regulating ANP32B function within the nucleus.…”
Section: Nuclear Localization Is What Matters: Converting CC From a Kmentioning
confidence: 99%
“…A study on breast cancer showed that ANP32B is necessary not only for the normal development of the body but also for the growth of breast cancer cells [ 31 ]. In the only study on ANP32B and HCC, downregulation of ANP32B played an antiapoptotic effect, but upregulation of ANP32B did not lead to apoptosis of HCC cells [ 9 ]. ANP32E can promote cell proliferation in mammals and plays a role in DNA repair and the cell cycle [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to adhere to the view of Reilly et al that only ANP32A, ANP32B, and ANP32E can truly be considered members of the ANP32 family in mammals [7]. Members of the ANP32 family participate in various molecular biological processes, such as embryonic development, chromatin modification and reconstruction, and apoptosis, by regulating cell signals and gene expression [7][8][9]. Many studies have shown that members of the ANP32 family are differentially expressed in certain cancers, such as pancreatic cancer, prostate cancer, breast cancer, glioblastoma, and leukemia, playing tumor-suppressive and oncogenic roles [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The acidic (leucine-rich) nuclear phosphoprotein 32 family member B ( ANP32B ), belong to the acidic nuclear phosphoprotein 32 (ANP32) family. ANP32B can modulate phosphorylation of Bad and expression of Bak/Bax , thus regulating apoptosis in HCC ( 24 ). Repair of damaged DNA relies on nucleosome dismantling of the nucleosome by histone chaperones and de-phosphorylation events carried out by Protein Phospatase 2A (PP2A) ( 25 ).…”
Section: Discussionmentioning
confidence: 99%